Evaluation of Response to Stereotactic Radiosurgery in Brain Metastases Using Multiparametric Magnetic Resonance Imaging and a Review of the Literature. Issue 1 (January 2019) - Sawlani, V.; Davies, N.; Patel, M.; Flintham, R.; Fong, C.; Heyes, G.; Cruickshank, G.; Steven, N.; Peet, A.; Hartley, A.; Benghiat, H.; Meade, S.; et al.
Abstract: Aims: Following stereotactic radiosurgery (SRS), brain metastases initially increase in size in up to a third of cases, suggesting treatment failure. Current imaging using structural magnetic resonance imaging (MRI) cannot differentiate between tumour recurrence and SRS-induced changes, creating difficulties with patient management. Combining multiparametric MRI techniques, which assess tissue physiological and metabolic information, has shown promise in answering this clinical question. Materials and methods: Multiparametric MRI techniques, including spectroscopy, diffusion and perfusion imaging, were used for the differentiation of radiation-related changes and tumour recurrence after SRS for intracranial metastases in six cases. All patients presented with enlargement of the treated lesion, an increase in perilesional brain oedema and aggravation or appearance of neurological signs and symptoms from 7 to 29 weeks after primary treatment. Results: Multiparametric imaging helped to differentiate features of tumour progression ( n  = 4) from radiation-related changes ( n  = 2). A low apparent diffusion coefficient (ADC) <1000 × 10 −6  mm 2 /s, high relative cerebral blood volume (rCBV) ratio > 2.1, high choline:creatine (Cho:Cr) ratio > 1.8 suggested tumour recurrence. A high ADC > 1000 × 10 −6  mm 2 /s, low rCBV ratio < 2.1, Cho:Cr ratio < 1.8 suggested SRS-induced radiation changes. Multiparametric MRI diagnosis was confirmed by histology or radiological and clinical follow-up. Conclusion: Multiparametric MRI was helpful in the early identification of radiation-related changes and tumour recurrence and may be useful for monitoring treatment changes in intracranial neoplasms after SRS treatment. Highlights: MRI cannot reliably differentiate tumour recurrence from radiation change in brain metastases. Multiparametric MRI including DWI, PWI and MRS may improve diagnostic accuracy. Low ADC <1000, high rCBV ratio >2.1, high Cho:Cr ratio >1.8 imply tumour recurrence. High ADC >1000, low rCBV ratio <2.1, Cho:Cr ratio <1.8 imply radiation changes.